Pelestarian Lacak sebagai Warisan Budaya Melayu Jambi di Desa Teluk, Kecamatan Pemayung, Kabupaten Batanghari Jambi - Fatonah, Fatonah; Hudaya, Padhil; Defrianti, Denny; Rahman, Abd; Siregar, Isrina; Resiyani, Wulan; Bahri, Zainul (Penerbit Widina, Widina Media Utama, 2025)
Lacak is one of the unique cultural heritages of the Malay people of Jambi, possessing high historical and philosophical value. Its existence is not only a symbol of regional pride, but also reflects the identity of the Malay people, who uphold the values of honor and wisdom. However, amid the tide of modernization and changing lifestyles among the younger generation, interest in learning about and preserving traditional cultures such as lacak is declining. Based on these issues, a team of lecturers from the University of Jambi carried out a community service activity with the theme “Preservation of Lacak as a Cultural Heritage of the Malay People of Jambi” which was held on October 4, 2025, in Teluk Village, Pemayung District, Batanghari Regency. This activity included training in making lacak, guided by Jambi cultural expert Zainul Bahri, and attended by local school children and teenagers. In addition to the training, a cultural quiz was held on lacak and historical figures of Jambi, such as Sultan Thaha Saifuddin and Raden Mattaher. The results of the activity showed an increase in participants' knowledge about the meaning and form of lacak, as well as a growing enthusiasm for preserving local culture. This activity successfully served as an educational and recreational means of strengthening the cultural identity of the Teluk Village community.ABSTRAKLacak merupakan salah satu warisan budaya khas Melayu Jambi yang memiliki nilai historis dan filosofis tinggi. Keberadaannya tidak hanya menjadi simbol kebanggaan identitas daerah, tetapi juga mencerminkan jati diri masyarakat Melayu yang menjunjung tinggi nilai kehormatan dan kebijaksanaan. Namun, di tengah arus modernisasi dan perubahan gaya hidup generasi muda, minat untuk mengenal dan melestarikan budaya tradisional seperti lacak semakin menurun. Berdasarkan permasalahan tersebut, tim dosen dari Universitas Jambi melaksanakan kegiatan pengabdian kepada masyarakat dengan tema “Pelestarian Lacak sebagai Warisan Budaya Melayu Jambi” yang dilaksanakan pada tanggal 4 Oktober 2025 di Desa Teluk, Kecamatan Pemayung, Kabupaten Batanghari. Kegiatan ini meliputi pelatihan pembuatan lacak yang dipandu oleh budayawan Jambi, Zainul Bahri, serta diikuti oleh anak-anak sekolah dan remaja setempat. Selain pelatihan, juga diselenggarakan kuis budaya mengenai lacak dan tokoh sejarah Jambi seperti Sultan Thaha Saifuddin dan Raden Mattaher. Hasil kegiatan menunjukkan meningkatnya pengetahuan peserta tentang makna dan bentuk lacak, serta tumbuhnya semangat pelestarian budaya lokal. Kegiatan ini berhasil menjadi sarana edukatif dan rekreatif dalam memperkuat identitas budaya masyarakat Desa Teluk.